VIRTUAL REALITY - SHOWS A NEW VISION FOR TOURISM AND HERITAGE - Guerra, José Paulo; Pinto, Miguel Moreira; Beato, Cláudia (European Scientific Journal, ESJ, 2015)
Observe the heritage, a monument, architecture or a sculpture and immediately receive useful additional information to interpret better. This is one of the promises of virtual reality technology. The concept of virtual reality is far from being a new concept. Many experiments on ways to overcome layers of information, in addition to the real world elements, in live observation, have been made over the past decade, exploring different types of use, in leisure and professional contexts. Improving the perception of reality, in contrast to virtual reality, offers other initiatives that replace the context of a simulated world, and the possibility of using an interactive way to manipulate it in a digitally way. Those are the latest achievements that have opened new evolution perspectives of virtual reality. The idea behind most computer applications is to improve the user interaction with the real world, adding information through the use of tools and techniques that were confined to the digital world. But those applications could be used on tourism orientation in cities and in the professional world, in diverse areas, as architecture in the BIM environment or interior design architecture, with the projection of elements like the furniture and could be visualized in the virtual space. The ability to draw, could verify and share new realities, that was already being exploited by companies, which add new layers of information to be used in their catalogs and products that literally transform the hybrid PC, tablets and smartphones customer in additional information sources, that lead to know better what is observed, but in tourism and heritage that virtual reality is being used more intensively. Virtual Reality could be a good way to travel and understand the touristic world.